'No, YOU make it!': Outsourcing production to fashion consumers to mediate labour. (1st October 2021) - Øien, Ida Falck; Zanon, Johanna
This practice-based article examines an attempt to reconnect fashion labour with value, after the fast fashion system increased the gap between the two. Developed by Norwegian fashion brand and collective platform HAiKw/ (Harald Lunde Helgesen and Ida Falck Øien), the Drop-in Factory was a fashion design experiment conducted at the non-profit art space Kunsthall Oslo in 2019. In this experiment, labour was outsourced to consumers-visitors, who by contract paid for equipment rental and training, earning 'Factory Coins' that could only be spent on the finished product. Inviting amateurs to make their own garment in a workshop setting has become a common strategy of design activism in fashion. However, instead of focusing on teaching individuals craft expertise, the Drop-in Factory explored collective making practices in an industrial-like environment, inspired by manufacturing and scientific management. Tensions arose over pay when some participants felt that their labour was unfairly compensated. As a response, roleplaying emerged from the experiment. Interviews of participants, conducted months later, incidentally echoed roleplay debriefing sessions. Their accounts show that they acquired labour literacy and embodied knowledge of fashion manufacturing, which extended to contracts and remuneration. While it remains unclear whether the Drop-in Factory led participants to revalue fashion labour, audience participation itself became the mediation of fashion labour.